Portfolio Aplikasi Proses Monitoring dan Evaluasi Proyek Pinjaman Luar Negeri - Kridalukmana, Rinta (Jurnal Sistem Komputer, 2011)
Diversity of managing data caused by some application that have same function and data. In monitoring and evaluation process of loan project, there are 2applications that have diversity problem. Those application are e-Monitoring and database Monev. The condition of Information Technology infrastructure also impact the applications performance. Application portfolio is crystallized from information system strategy, information technology strategy and managing information system strategy that have been developed before, so that the portfolio could be one solution to handle diversity problem.In this research, application portfolio will be developed byusing IS/IT (Information System/Information Technology)Strategic Model of J.Ward and J.Peppard.